Limestone reaction in calcium aluminate cement–calcium sulfate systems. (October 2015) - Bizzozero, Julien; Scrivener, Karen L.
Abstract: This paper reports a study of ternary blends composed of calcium aluminate cement, calcium sulfate hemihydrate and limestone. Compressive strength tests and hydration kinetics were studied as a function of limestone and calcium sulfate content. The phase evolution and the total porosity were followed and compared to thermodynamic simulation to understand the reactions involved and the effect of limestone on these binders. The reaction of limestone leads to the formation of hemicarboaluminate and monocarboaluminate. Increasing the ratio between sulfate and aluminate decreases the extent of limestone reaction.